(untitled) (Medico Legal Update, 2021)
Introduction: Stingless bee honey has different characteristics from other types of bee honey in terms of colors, tastes, water content, and sugar. Trigona honey is one of the local products in South Sulawesi produced by stingless bees from Tetragonula species widely known to the public. This study determined the phenol content of trigona honey and its antioxidant activity. Method: The compounds of trigona honey ethanol extract were identified using gas chromatography. The antioxidant activity of the extract was examined with the DPPH method. Result Content test shows that trigona honey has bioactive compounds, flavonoids, alkaloids, and triterpenoids. DPPH show to trigona honey 104,25. Conclusion: Trigona honey contains mild antioxidant activity and metabolite compounds such as polyphenols, flavonoids, alkaloids, and triterpenoids. The nutrient activity can reduce blood glucose and increase insulin plasma.